2013
DOI: 10.2478/ecoq-2013-0009
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian situation in urban environment – history of the common toad Bufo bufo in Kraków (Poland)

Abstract: Rapid urbanization processes are not neutral to the environment, especially amphibians. Their double-environment lifestyle makes them particularly vulnerable to negative changes in the environment. Inventory research on batrachofauna carried out in urban areas usually provides data on its current state, but there is little information about changes in its composition over the years. The aim of the study was to investigate the situation of amphibians in urban areas of Kraków (Poland) over the last 90 years. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…Assuming, that all water bodies were characterized then by a similar species composition, the condition of their water could also be similar. Our research revealed that water bodies identified as HES were in majority, which proves the loss of amphibian species and is consistent with the previous studies (Guzik et al 1996;Kawa et al 2011;Budzik et al 2013). As we expected, the values of most chemical indicators were higher in HES than in LES.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Assuming, that all water bodies were characterized then by a similar species composition, the condition of their water could also be similar. Our research revealed that water bodies identified as HES were in majority, which proves the loss of amphibian species and is consistent with the previous studies (Guzik et al 1996;Kawa et al 2011;Budzik et al 2013). As we expected, the values of most chemical indicators were higher in HES than in LES.…”
Section: Discussionsupporting
confidence: 93%
“…1) was not a random sample, because it was prepared on the basis of data from the previous inventory in the years 1986years -1992years (Guzik et al 1996. Although our sample size is fairly small, it seems to be representative, in terms of historical amphibian species presence (Guzik et al 1996) and their current state (Kawa et al 2011;Budzik et al 2013). Three amphibian species (Hyla arborea, Pelobates fuscus, Pseudepidalea viridis), which were noted by Guzik (1996), were not found in 15 currently investigated water bodies.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations